Evaluation of substrates for mass multiplication of green manure associated fungi for biological control of soil borne phytopathogens - SEWETA SRIVASTAVA; SAURABH SINGH, RAVINDRA KUMAR*, ASHA SINHA (Indian Phytopathology, 2014)
Inhibitory potential of dominant decomposing fungi of Sesbania green manure was evaluated against some important soil borne plant pathogens viz., Athelia rolfsii, Rhizoctonia solani and Sclerotinia sclerotiorum by dual culture methods. The selected dominant decomposing fungi were also evaluated for its mass production on different substrates. Maximum growth inhibition of Sclerotium rolfsii, Rhizoctonia solani and Sclerotinia sclerotiorum observed in dual culture with Trichoderma harzianum after 96 hours were 57.03%, 58.42% and 64.81%, respectively. The mean colonial diameter of Sclerotium rolfsii, Rhizoctonia solani and Sclerotinia sclerotiorum was found minimum by the effect of cultural filtrates and volatile metabolites of Trichoderma harzianum, Aspergillus niger and Penicillium citrinum among all the dominant fungi. Four different substrates viz., pearl millet, wheat, sorghum and Sesbania aculeata L. were evaluated for their potentiality to be a candidate substrate for effective and successful mass production of dominant decomposing fungi used as potential biological control agents. The efficacy was measured in terms of spore production of the fungal species and loss in the weight of the substrates. Aspergillus fumigatus recorded maximum population (130.64 x 106spore g-1) when mass cultured on pearl millet grains substrate. The minimum population of spore was recorded in Curvularia lunata (6.55 x 106 spore g-1) on Sesbania aculeata substrate. The maximum per cent weight loss was recorded in Penicillium citrinum inoculated on pearl millet grains (48.75%) and the minimum per cent weight loss was observed in Curvularia lunata inoculated on Sesbania aculeata (14.75%).